2021
DOI: 10.1039/d1gc01521d
|View full text |Cite
|
Sign up to set email alerts
|

Controlling bacterial contamination during fuel ethanol fermentation using thermochemically depolymerized lignin bio-oils

Abstract: Lactic acid bacteria (LAB) contamination during fuel ethanol fermentation can lead to significant economic loses. To circumvent this, fuel ethanol plants add antibiotics prophylactically, but their overuse has resulted in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The principal route explored for lignin valorization is its conversion into aromatic compounds via depolymerization. Various methods have been invested to depolymerize lignin into phenolic chemicals such as acid/based-catalyzed depolymerization, [1] oxidative depolymerization, [2] thermochemical depolymerization, [3] hydrodeoxygenation, [4] solvolysis, [5] and supercritical depolymerization. [6] However, those processes are usually energy intensive and environmentally unfriendly.…”
Section: Introductionmentioning
confidence: 99%
“…The principal route explored for lignin valorization is its conversion into aromatic compounds via depolymerization. Various methods have been invested to depolymerize lignin into phenolic chemicals such as acid/based-catalyzed depolymerization, [1] oxidative depolymerization, [2] thermochemical depolymerization, [3] hydrodeoxygenation, [4] solvolysis, [5] and supercritical depolymerization. [6] However, those processes are usually energy intensive and environmentally unfriendly.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, alkaline enzymatic lignin was depolymerized by PAA (0.8 g PAA/g lignin) with a 36.1% yield of monomers. 12 Ma et al reported that two kinds of lignin depolymerization occurred in the presence of PAA, with a yield of phenolic compounds (less than 22%). 13 Despite the effective oxidative cracking of lignin, some of them suffered from certain drawbacks, such as limited selectivity and poor product yield.…”
Section: Introductionmentioning
confidence: 99%
“…Electrophilic PAA can work on electron-rich sites (e.g., aromatic ring and olefinic site) in lignin, resulting in the conversion of lignin into small molecular weight fragments. For instance, alkaline enzymatic lignin was depolymerized by PAA (0.8 g PAA/g lignin) with a 36.1% yield of monomers . Ma et al reported that two kinds of lignin depolymerization occurred in the presence of PAA, with a yield of phenolic compounds (less than 22%) .…”
Section: Introductionmentioning
confidence: 99%